Autophagy activation is involved in 3,4-methylenedioxymethamphetamine ('ecstasy')--induced neurotoxicity in cultured cortical neurons. - I-Hsun Li; Kuo-Hsing Ma; Shao-Ju Weng; Shiang-Suo Huang; Chang-Min Liang; Yuahn-Sieh Huang (PLoS ONE, 2014)
Autophagic (type II) cell death, characterized by the massive accumulation of autophagic vacuoles in the cytoplasm of cells, has been suggested to play pathogenetic roles in cerebral ischemia, brain trauma, and neurodegenerative disorders. 3,4-Methylenedioxymethamphetamine (MDMA or ecstasy) is an illicit drug causing long-term neurotoxicity in the brain. Apoptotic (type I) and necrotic (type III) cell death have been implicated in MDMA-induced neurotoxicity, while the role of autophagy in MDMA-elicited neurotoxicity has not been investigated. The present study aimed to evaluate the occurrence and contribution of autophagy to neurotoxicity in cultured rat cortical neurons challenged with MDMA. Autophagy activation was monitored by expression of microtubule-associated protein 1 light chain 3 (LC3; an autophagic marker) using immunofluorescence and western blot analysis. Here, we demonstrate that MDMA exposure induced monodansylcadaverine (MDC)- and LC3B-densely stained autophagosome formation and increased conversion of LC3B-I to LC3B-II, coinciding with the neurodegenerative phase of MDMA challenge. Autophagy inhibitor 3-methyladenine (3-MA) pretreatment significantly attenuated MDMA-induced autophagosome accumulation, LC3B-II expression, and ameliorated MDMA-triggered neurite damage and neuronal death. In contrast, enhanced autophagy flux by rapamycin or impaired autophagosome clearance by bafilomycin A1 led to more autophagosome accumulation in neurons and aggravated neurite degeneration, indicating that excessive autophagosome accumulation contributes to MDMA-induced neurotoxicity. Furthermore, MDMA induced phosphorylation of AMP-activated protein kinase (AMPK) and its downstream unc-51-like kinase 1 (ULK1), suggesting the AMPK/ULK1 signaling pathway might be involved in MDMA-induced autophagy activation.